A guide to effective school leadership theories - Lynch, Matthew (London, United Kingdom : Routledge, 2012)
A Guide to Effective School Leadership Theories provides an exploration of ten dominant leadership strategies to give school leaders a solid basis in theory and practical application. Demonstrating the advantages and drawbacks of each theory, readers are encouraged to discover the most appropriate strategy, or combination of strategies, that will best enable their school.
1. Transformational Leadership : The (Un)Disputed Champion of Leadership Strategies -- 2. Instructional Leadership : A Catalyst for the Promotion of Teaching and Learning -- 3. Distributed Leadership : A Humanistic Approach to Shared Governance -- 4. Ethical Leadership : Using Your Moral Compass to Steer the Ship -- 5. Emotional Leadership : Using Your Heart to Lead -- 6. Entrepreneurial Leadership : How Schools can Learn from Business Leaders -- 7. Strategic Leadership : Those Who Fail to Plan, Plan to Fail -- 8. Sustainable Leadership : The Race is Won by Those Who Endure -- 9. Invitational Leadership : Developing a School Culture of Trust, Respect, and Hope -- 10. Constructivist Leadership : A Framework for Building Sustainable School Improvement
Includes bibliographical references and index.
Keywords: EDUCATIONAL LEADERSHIP